Diplopods as Bioindicators of Soils: Analysis of Midgut of Individuals Maintained in Substract Containing Sewage Sludge - Preto de Godoy, Juliana Aparecida [UNESP]; Fontanetti, Carmem S. [UNESP] (Springer, 2010)
Diplopods feed organic matter in decomposition; however, some environmental factors can promote changes in tissues of these animals. Sewage sludge has been applied for recuperation of physical structure of degraded soil. This work analyzed the influence of the sludge from a city of So Paulo in the midgut of the diplopod Rhinocricus padbergi. After the exposition to sludge, the midgut was prepared for histological and ultra-structural analyses. After 1 week of exposition, there were various glycoprotein globules in the fat body, which appeared, ultrastructurally, little electron dense. In the animals exposed for 2 weeks, there was an intensive renovation of the epithelium with the invasion of regenerative cells, which was observed in the histological and ultra-structural analyses. These data showed that the sludge present various substances that were very hazardous for these animals; more studies were necessary before the application of this in agriculture.
Keywords: Digestive tract; Soil fauna; Globules; Epithelium renovation